THE HISTORY OF BEKS DURING THE BUKHARA EMIRATE PERIOD (THE CASE OF KASHKADARYA PROVINCE) - Umar Ergashev; Sabrina Rizvonova (Western European Studies, 2025)
This article analyzes the political, economic, and cultural significance of the Kashkadarya province during the Bukhara Emirate period. Kashkadarya, as an important region outside of Bukhara, played a crucial role due to its strategic location, the intersection of trade routes, and its natural resources. The province’s agricultural activities, craftsmanship, and trade contributed significantly to the economic stability of the Bukhara Emirate. Additionally, the political and social processes in Kashkadarya had a profound influence on the policies of the Emirate. The cultural and intellectual life of the province, especially its madrasas, scientific centers, and architectural monuments, played a vital role in shaping the cultural heritage of the Bukhara Emirate. This article providesinsight into the role and significance of the Kashkadarya province during the Bukhara Emirate period
Keywords: Bukhara Emirate; Kashkadarya province; political significance